DETERMINISME TEKNOLOGI DALAM KETERGANTUNGAN ARTIFICIAL INTELLIGENCE PADA PROSES PEMBELAJARAN MAHASISWA - Maria Nona Desty; Imanta I. Perangin Angin; Hotlif A. Nope; Lenny S. Bire Manoe (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Abstract: This study aims to analyze how Artificial Intelligence (AI) dependency emerges in the learning process among 2022 students of the Faculty of Social and Political Sciences, Universitas Nusa Cendana. A qualitative approach with a case study method was employed. Data were collected through observation, in-depth interviews, and documentation involving 14 informants selected using purposive sampling. The findings reveal that AI dependency develops through students' adaptation to digital technology, as reflected in the use of AI as the primary source for understanding course materials, searching for initial references, and completing academic assignments. This dependency is driven by academic workload, time constraints, ease of access, and students' perceptions of AI as an efficient learning tool. While AI enhances learning efficiency and supports idea generation, excessive reliance on it may reduce critical thinking skills, conceptual understanding, and independent learning. These findings reinforce Marshall McLuhan's Technological Determinism Theory, demonstrating that technology shapes students' learning behaviors and strategies in the digital era.Keywords: Artificial Intelligence, Dependency, Learning Process, Technological Determinism, University Students.